GILBERTO LEX SCHOOL'S STRATEGIES FOR INCREASING ITS IDEB - Escame Gimiliani, Tiago (Revista Gênero e Interdisciplinaridade, 2024)
This research focused on the Municipal School Gilberto Lex in Tarumã, São Paulo, as a success case in IDEB indicators and evaluated the strategies the school developed that may have led to the improvement of its indexes in the state and also in the country. Through research with school data and public websites, we verified that this educational institution adopted active methodology, especially project-based pedagogy in its practices, breaking with traditional teaching methodology. The student then became the protagonist of their learning, which may have led to increased learning and, as a result, improved indicators.